1995
DOI: 10.1007/bf00051933
|View full text |Cite
|
Sign up to set email alerts
|

Repellent and acaricidal properties of Ocimum suave against Rhipicephalus appendiculatus ticks

Abstract: An oil extracted from the leaves of a tropical shrub Ocimum suave was found to repel as well as kill all stages of the tick Rhipicephalus appendiculatus. In an in vitro bioassay for the larvae, the LC50 of the oil in liquid paraffin was 0.024%. A 10% solution was found to kill all immatures and more than 70% of adults feeding on rabbits. Rabbits were protected for 5 days against attaching larvae using a 10% solution. Preliminary experiments undertaken with cattle kept in the field suggest that the oil may have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0
5

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(37 citation statements)
references
References 9 publications
1
31
0
5
Order By: Relevance
“…Finally, several studies have reported insecticidal and acaricidal activities from essential oils and isolated compounds from Ocimum genus (Mwangi et al 1995;Kéita et al 2000;2001;Pavela 2004Pavela , 2008Murugan et al 2007;Kostic et al 2008;Del Fabro and Nazzi 2008). Interestingly, there is some evidence indicating that derived components obtained from this genus have repellent activity against insects and ticks.…”
Section: Resultsmentioning
confidence: 98%
“…Finally, several studies have reported insecticidal and acaricidal activities from essential oils and isolated compounds from Ocimum genus (Mwangi et al 1995;Kéita et al 2000;2001;Pavela 2004Pavela , 2008Murugan et al 2007;Kostic et al 2008;Del Fabro and Nazzi 2008). Interestingly, there is some evidence indicating that derived components obtained from this genus have repellent activity against insects and ticks.…”
Section: Resultsmentioning
confidence: 98%
“…Of all the extracted fractions screened, hexane fraction with 3WPI value showed the best grain protectant activity (Table 3). From the results of the phytochemical screening, some phytocompounds identified have previously been associated with repellency activity [73,74,103]. The principal constituent of the essential oil of O. gratissimum is eugenol which is responsible for the biological activities observed.…”
Section: Resultsmentioning
confidence: 99%
“…Earlier reports have also shown the smooth muscle contracting and antimutagenic activity [62] as well as its anti-diarrhoeal effects in experimental animals [63], high antiviral indices against HIV-1 and HIV-2 [64]; shigellocidal properties [65,66], anti-trypanosomal effects [67], immunobiologicalactivity [68], gastroprotective properties [69], controlling agent for food spoilage and mycotoxin producing fungi [70], disintegrant properties of its seed mucilage [71], and as a relaxant on isolated ileum from guinea pig [72]. Its essential oil has mosquito repellant, insecticidal properties [73,74]. The essential oil of O. gratissimum and its main component eugenol were reported to be efficient in inhibiting Haemonchus contortus [75,76].…”
Section: Introductionmentioning
confidence: 99%
“…. Diversos autores avaliaram óleos essenciais e compostos isolados de plantas do gênero Ocimum e constataram que estes fitoterápicos possuem ação inseticida e acaricida (MWANGI et al, 1995;MURUGAN;MURUGAN;NOORTHEN, 2007, KOSTIC et al, 2008DEL FABRO;NAZZI, 2008). Kostic et al (2008) testando óleo essencial de manjericão sobre larvas de Lymantria dispar constataram que este fitoterápico apresentou baixa toxicidade e alta ação na inibição da alimentação das mariposas, provocando assim a sua morte.…”
Section: Introductionunclassified
“…Kostic et al (2008) testando óleo essencial de manjericão sobre larvas de Lymantria dispar constataram que este fitoterápico apresentou baixa toxicidade e alta ação na inibição da alimentação das mariposas, provocando assim a sua morte. Mwangi et al (1995) …”
Section: Introductionunclassified